Suicidal ideation in an Egyptian sample of hospitalized patients with acute psychosis. Issue 3 (2nd July 2020) - Mubarak, Ahmed A.; Gad, El-Sayed; Saada, Sameh; Ftouh, Maha; Seleem, Mohammad A.
ABSTRACT: Background : Suicide mortality is 12 times higher in psychotic patients compared to the general population. Identifying the characteristics of suicidal patients among this group might help in preventing such behavior. Aims : To assess the predictors of suicidal risk in patients hospitalized due to acute psychosis. Methods : A total of 150 patients (age 18–60 years) admitted with acute psychotic features were recruited. Patients were evaluated clinically by the Arabic version of Mini International Neuropsychiatric Interview (MINI.) Suicidal ideation was assessed using the Scale for Suicide Ideation (SSI). Results : Forty-four out of 150 patients (29.33%) reported having current and/or previous history of suicidal ideation. Patients with major depression showed the highest suicidal tendencies followed by delusional disorder, bipolar disorder, psychosis related to substance abuse and schizophrenia. The more severe the psychotic symptoms, the more suicidal tendencies shown by patients. Predictors for suicidal ideation included diagnostic category, severity of psychotic features, unemployement and younger age. Conclusion : Patients with psychosis that require admission to hospital carry a high risk of suicidal ideation and behavior. Factors like unemployment, young age, psychiatric diagnosis and severity of psychosis could be predictors for suicidal ideation.